PENGARUH SIKLUS HIDUP DAN UKURAN PERUSAHAAN TERHADAP EARNING MANAGEMENT PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Kusumawati, Endang; Cahyati, Ari Dewi (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2014)
Title: [Life Cycle and Company Size Effect on Earning Management of Corporates are Listed on Indonesia Stock Exchange]The study goal was to determine whether there is influence of the life cycle and firm size on earnings management in companies listed on the Stock Exchange Indonesia. Data tehnique collection is done by purposive sampling. The data used in this study is secondary data, engineering data collection is done by purposive sampling. The total sample of 78 manufacturing companies. The results showed that the life cycle variables significant positive effect on earnings management practices while the firm size variable is not significant effect on earnings management practices. In general it can be concluded that the only variable that has a life cycle just significant positive effect on earnings management. Subsequent researchers expected to add other factors influence earnings management as another independent variable, because it is possible that other factors not included in this study influence the practice of earnings management.